Prototipe Rancang Bangun Sistem Informasi Anti Bullying Dan Cyberbullying Berbasis Web - Widoyoningrum, Sri; Laili, Elisa Nurul; Ali, Mahrus; Lazulfa, Indana; Indriawan, Fani; Andriani, Anita; Indriyanti, Aries Dwi (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
In recent years (2020-2023), bullying and cyberbullying cases have shown an increasing trend based on data from the Indonesian Child Protection Commission (KPAI), the Federation of Indonesian Teachers' Unions (FSGI), and Kabarbursa online media. Throughout 2023, FSGI data recorded around 30 bullying cases, with 80% occurring in schools under the auspices of the Ministry of Education and Culture Ristek, and the rest in schools managed by the Ministry of Religious Affairs.The total number of bullying cases recorded reached 1,478, indicating the need for more attention to a safe school environment for students . The method of designing a web-based anti-bullying and cyberbullying information system uses the system development stages of the Borg & Gall model. The purpose of designing a web-based anti-bullying and cyberbullying information system prototype in utilising technology as an effort to create a safe environment, especially in the school environment and foster a culture of mutual respect and safety as well as proactive action efforts to create positive changes in the environment.